Florida LAKEWATCH and Aquatic Bird Surveys: A Winning Combination - Ashley H. Traut; Mark E. Hostetler; Eric J. Schulz; Mark V. Hoyer (EDIS)
This document is Fact Sheet WEC 166, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published in October 2002.